Ks. Jarosław Babiński, Irreligia, Pelplin: Wydawnictwo Bernardinum 2010, ss. 128. - Lewandowski, Jerzy (Teologia w Polsce, 2020)
Recenzja książki: Ks. Jarosław Babiński, Irreligia, Pelplin: Wydawnictwo Bernardinum 2010, ss. 128.